KONSEP BIMBINGAN TAZKIYATUN NAFS DALAM MEMBENTUK SIKAP JUJUR MAHASISWA BKI MELALUI PEMBIASAAN (CONDITIONING) - LUKMAN NULHAKIM (Al-Tazkiah : Jurnal Bimbingan dan Konseling Islam, 2019)
This paper aims to offer the concept of tazkiyatun nafs guidance as a solution for personality guidance for prospective Islamic counselors to form a commendable attitude, one of which is honest attitude by prioritizing aspects of religiosity of students. Providing tazkiyatun nafs guidance through the habituation method by the counselor, positioning the counselor helps to be a reminder of the inner order that has its own rules. Physiological and psychological circumstances are the essential basis of human personality